Study of Cascade System under Reliability Theory for Different Distributions: Assessment of System Reliability using Different Distributions in Cascade Systems (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper we have considered diverse distribution to acquire the system reliability of a n-course system. The assessment of reliability is considered primarily for course systems. For this reason, a few distributions are considered specifically, exponential, Weibull, gamma, Rayleigh, Lindley, uniform and two-point distribution. At that point some notable distributions in particular, exponential, gamma and Weibull distribution are utilized to assess the reliability of n - course system. The numerical values R(1), R(2), R(3) and R3 have likewise been processed and given in unthinkable structures to some particular values of the parameters.